Recruitment of the human Cdt1 replication licensing protein by the loop domain of Hec1 is required for stable kinetochore microtubule attachment - Varma, Dileep (2012)
Cdt1, a protein critical for replication origin licensing in G1 phase is degraded during S phase but re-accumulates in G2 phase. We now demonstrate that human Cdt1 has a separable essential mitotic function. Cdt1 localizes to kinetochores during mitosis through interaction with the Hec1 component of the Ndc80 complex. G2-specific depletion of Cdt1 arrests cells in late prometaphase due to abnormally unstable kinetochore-microtubule (kMT) attachments and Mad1-dependent spindle assembly checkpoint activity. Cdt1 binds a unique loop extending from the rod domain of Hec1 that we show is also required for kMT attachment. Mutation of the loop domain prevents Cdt1 kinetochore localization and arrests cells in prometaphase. Super-resolution fluorescence microscopy indicates that Cdt1 binding to the Hec1 loop domain promotes a microtubule-dependent conformational change in the Ndc80 complex in vivo. These results support the conclusion that Cdt1 binding to Hec1 is essential for an extended Ndc80 configuration and stable kinetochore microtubule attachment.